Toxicity of dietary Heliotropium dolosum seed to Japanese quail - Eroksuz, Y; Eroksuz, H; Ozer, H; Ilhan, N; Cevik, A; Yaman, I; Ceribasi, AO (Comparative Toxicology Lab, 2002)
Five groups of 30 male Japanese quail, each 7-w-old, were fed diets containing 0, 1, 3, S, or 10% (w/w) of dehulled H dolosum Seed. Half of the birds from the each group were killed at 6 and 24 w after beginning of the trial. At the end of 6(th) w, neither mortality nor clinical sign occurred in test groups. In the 5 and 10% inclusion levels, mild to moderate hepatic injury was detected as evidenced by mild karyomegaly, moderate fatty change, focal or portal fibrosis, bile duct hyperplasie, and ovalocyte proliferation along with lower serum protein and albumin levels. By the termination of the experiment (24 w), 5 birds died in the 10% dosed group. Hepatic cirrhosis was the most prominent finding in the 5 and 10% group; at these levels, serum protein and albumin values decreased significantly while billuribin and ALP levels increased. Based on relative weights and histological evaluations, testicular atrophy was dose dependent. These results partly affirm earlier studies that the Quail is highs resistant to the toxic effects of H dolosum seed. However, the resistance to H dolosum is less than Senecio jacobae and Crotalaria spectabilis when considering tissue injury.
Keywords: Pyrrolizidine Alkaloids; Metabolism